Successful Neoadjuvant Therapy with Pembrolizumab Monotherapy for Advanced Ascending Colon Cancer - Chien-Tzu Huang*; Jeng-Shiun Du (Journal of Cancer Research and Practice)
Immune checkpoint inhibitors have emerged as an effective standard of care for deficient mismatch repair (dMMR)/high microsatellite instability (MSI-H) metastatic colorectal cancer (CRC). However, the role of immunotherapy in the neoadjuvant setting remains uncertain. We report a patient with advanced colon cancer who received curative surgery after successful treatment with pembrolizumab monotherapy. She remains in complete remission after 16 months following the first diagnosis without any immune-related adverse events. In conclusion, single-agent pembrolizumab has strong potential in neoadjuvant therapy for patients with dMMR/MSI-H advanced CRC.